Efek Penambahan Tepung Daun Kelor (Moringa Oleifera) Pada Ransum Komersial Terhadap Berat Karkas, Persentase Karkas dan Persentase Non Karkas Ayam Broiler - Jery Daku Haril; Yan Tonga; I Nyoman Kaca (GEMA AGRO, 2018)
One of the efforts to fulfill the community's nutritional resources derived from animal protein is by broiler farming business. In order for broiler chickens to achieve optimal productivity then the provision of proper rations in both quality and quantity must be met, but the obstacle in improving the quality of the ration is the cost of ration is large enough. It is necessary to research the feed material that is able to meet the needs of broiler chicken one of them is the leaves kelor. This research used broiler strain CP-707 as much as 60 tail. The method used is CRD (Completely Randomized Design) with 5 treatments and 4 replications. The treatments were rations with no addition of moringa flour (PO), ration with addition of 3% maize flour (P1), ration with addition of 6% maize flour (P2), ration with addition of maize flour 9% (P3), ration with the addition of 12% maize flour (P4). The variables observed in this study were carcass weight, carcass percentage and non carcass percentage. From the results of this study it can be concluded that the addition of moringa flour on ration to 12% level on carcass weight, carcass percentage and non carcass percentage statistically show different not significant.